2008
DOI: 10.1016/j.rmed.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids during pregnancy: A review of methodologic issues

Abstract: While there currently is some degree of evidence to support the safety of ICS use during pregnancy, this review highlights the limited statistical power of several studies published in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Inhaled corticosteroids (ICS) represent a cornerstone in the management of asthma. Asthma guidelines recommend that pregnant asthma patients should be treated with ICS to the same degree as non-pregnant women (1). The lack of toxicity of ICS in the treatment of asthma during pregnancy has been reported in systematic reviews (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled corticosteroids (ICS) represent a cornerstone in the management of asthma. Asthma guidelines recommend that pregnant asthma patients should be treated with ICS to the same degree as non-pregnant women (1). The lack of toxicity of ICS in the treatment of asthma during pregnancy has been reported in systematic reviews (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…it is safer for pregnant women with asthma to be treated with asthma medications than it is for them to have asthma symptoms and exacerbations." [2] While inhaled corticosteroids (ICS) are considered the cornerstone therapy in the management of persistent asthma during pregnancy [9,10], beta 2 -agonists have a crucial role in asthma management [2]. During pregnancy, short-acting beta 2 -agonists (SABA) are used as reliever medications for all asthma types (mild, moderate, or severe), while long-acting beta 2 -agonists (LABA) are used in cases of moderate to severe persistent asthma, in combination with low or medium doses ofICS [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…1 Inhaled corticosteroids (ICSs) are recognized as the first-line controller therapy, and the same doses are recommended during pregnancy and under other circumstances. 1 In a recent literature review, 3 we identified 15 studies that investigated the risk of congenital malformations in association with the use of ICSs during pregnancy. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In 6 of these studies, [4][5][6][15][16][17] ICS users were compared with women with asthma who did not use any ICS during pregnancy, whereas in the other studies, ICS users were compared with the general population, women without asthma, or users of theophylline.…”
mentioning
confidence: 99%